Isolasi klorofil a dan analisis aktivitas antioksidan dari mikroalga C. vulgaris: Isolation of chlorophyll a and analysis of antioxidant activity from microalgae C. vulgaris - Chamidah, Anies; Afrilia, Hefni Citra; Ahmad, Mirza Gulam; Arisandi, Desy (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Chlorophyll is a green pigment found in the thylakoid membrane, consisting of chlorophyll a, b, c, d, and e, and is beneficial as an antioxidant, anti-inflammatory, antimutagenic, and anticancer agent. The use of chlorophyll from microalgae has not been extensively explored compared with that from terrestrial plants. This study aimed to isolate and determine the antioxidant activity of chlorophyll-a from C. vulgaris. The research method used was laboratory experiments, with stages including the extraction of C. vulgaris microalgae using 96% ethanol solvent, fractionation of crude C. vulgaris extract with n-hexane, chlorophyll identification and determination of the best eluent for TLC isolation, and fraction isolation to obtain chlorophyll pigments, followed by TLC testing, total chlorophyll content, and antioxidant activity. The test results included the yield test, thin-layer chromatography (TLC), total chlorophyll content, and antioxidant activity test using the DPPH method. The research results show that chlorophyll-a can be isolated through extraction using 96% ethanol, fractionation with n-hexane, and purification by column chromatography using a petroleum ether solvent. (7:3). The IC50 value of the produced chlorophyll-a is 63.99±5.46 ppm, which falls into the category of strong antioxidants. These findings indicate that the chlorophyll-a from C. vulgaris has the potential to be an effective source of natural antioxidants.